2002
DOI: 10.1046/j.1525-1470.2002.t01-1-00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgical Excision of a Complex Vascular Lesion in an Infant with Kasabach–Merritt Syndrome

Abstract: Kasabach-Merritt syndrome, the association of a vascular lesion and consumptive coagulopathy, can represent a diagnostic and therapeutic challenge to clinicians. We describe an infant with a large complex vascular lesion of the left forearm that was successfully surgically excised. We propose surgical excision as an appropriate therapeutic option for some cases of Kasabach-Merritt syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…27 Resection is possible in the rare instance of a small tumor. 15,28 In addition, arterial embolization may be effective in initiating regression. 29 Zukerberg et al 4 suggested that the prevalence of KHE is higher than indicated in published accounts because vascular tumors not manifested by coagulopathy and systemic involvement are less likely to be reported and examined histologically.…”
Section: Discussionmentioning
confidence: 99%
“…27 Resection is possible in the rare instance of a small tumor. 15,28 In addition, arterial embolization may be effective in initiating regression. 29 Zukerberg et al 4 suggested that the prevalence of KHE is higher than indicated in published accounts because vascular tumors not manifested by coagulopathy and systemic involvement are less likely to be reported and examined histologically.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach, however, remains a good option for small or medium‐sized lesions. Early one‐stage surgical resection (when possible) is a fast and effective treatment . It was particularly appropriate in the present case due to the pseudo‐pedicle aspect of the lesion.…”
Section: Discussionmentioning
confidence: 92%
“…Complete surgical excision is the most effective treatment of small KHE lesions (Drolet et al 2001; George et al 2002). However, tumor site or localization may prevent this treatment option.…”
Section: Resultsmentioning
confidence: 99%